2020
DOI: 10.1016/j.jsv.2020.115574
|View full text |Cite
|
Sign up to set email alerts
|

On the noise reduction mechanisms of porous aerofoil leading edges

Abstract: This paper is predominantly an experimental study into the reduction of turbulence -aerofoil interaction noise by the introduction of aerofoil porosity. In this paper we study three scenarios applied to flat plates: (a) when the flat plate is fully porous, (b) when the flat plate is partially porous from the leading edge and (c) when porosity is introduced downstream of the leading edge.This paper shows that the noise reduction spectra collapse when plotted against non-dimensional frequency f l/U , where l is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Recently, Chaitanya et al. (2020) proposed source-cutoff and edge-to-edge interference as the two main noise-reduction mechanisms for fully and partially porous flat plates, when in the porous section the porosity is uniformly distributed. A possible alternative explanation for the source cutoff is due to the presence of evanescent surface waves of the form by the impedance-type boundary condition of the form , as previously observed by Rienstra & Hirschberg (2004) (where ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Chaitanya et al. (2020) proposed source-cutoff and edge-to-edge interference as the two main noise-reduction mechanisms for fully and partially porous flat plates, when in the porous section the porosity is uniformly distributed. A possible alternative explanation for the source cutoff is due to the presence of evanescent surface waves of the form by the impedance-type boundary condition of the form , as previously observed by Rienstra & Hirschberg (2004) (where ).…”
Section: Resultsmentioning
confidence: 99%
“…This back scattering arises because a non-zero jump in pressure across the plate at the leading edge must be smoothly reduced to zero upstream of the plate. If the leading edge is porous, α L > 0, the back scattering is much weaker than if α L = 0, since there is communication between the upper and lower surfaces of the plate and the pressure jump across the plate at the (porous) leading edge is dampened (Chaitanya et al 2020). This gives rise to two possible reasons for noise reduction at low frequencies as we vary γ ; increased average plate porosity and back scattering effects result in edge-to-edge interference.…”
Section: Monotonic Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of reducing the turbulence interaction noise, different leading-edge modifications have been developed in the past that affect the aerodynamic and acoustic properties of the airfoil. For isolated airfoils or flat plates, these modifications basically consist of leading-edge serrations [4][5][6][7][8][9][10], comblike structures [11], and the application of flow-permeable or porous materials [12][13][14][15][16][17][18][19]. Noise reduction techniques such as serrations or porous materials have also been used in so-called rod-airfoil configurations, which are used to study rotor-stator interaction noise [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation of the tonal components of the emitted far-field noise was measured in this case. Paruchuri et al [24] studied the turbulence-interaction noise reduction obtained by flat plates characterized by different extents of porous inserts. Notably, they observed that the use of a single row of holes situated downstream of the leading edge allows for a significant low-frequency attenuation without increasing the noise radiations at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%